Overview of Custom Microcontroller using Xilinx Zynq XC7Z020 FPGA - Bayu Kanigoro; Ricky Efraim Lie; M. Fitra Kacamarga (Universitas Ahmad Dahlan, 2015)
This paper presents an overview of customizable microcontroller using a Xilinx Zynq XC7Z020 FPGA as an alternative to increase its performance as user need. This alternative arises due to many of the systems, which developed mostly by using microcontroller are not giving any room for customization to increase its performance or I/O ports. There is any possibility that the system designed to be used by using general processor such as PC to increase its performance but it will give another problem such as interface difficulty for high speed I/O, real time processing, increases complexity, and many more. Customization is introduced by combining hard IP processor and FPGA in one chip instead of practicing two separate devices, processor and FPGA, which is commonly use in high performance embedded design. This approach allows seamless design development and development time reduction for customization.